Application of Foam Mat Drying Method for the Production of Instant Red Ginger Powder using Microwave - Purbasari, Dian; Lestari, Wahyu Winda; Sutarsi, Sutarsi; Lestari, Ning Puji; Taruna, Iwan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Drying red ginger juice into instant powder is done to extend the shelf life of ginger which easily undergoes physical and chemical changes. This research aims to determine the characteristics of red ginger juice powder resulting from the foam mat drying method using a microwave. This research used a Completely Randomized Design method with two factors. Factor I is the microwave oven power (341 W, 364 W, and 466 W). Factor II is the concentration of maltodextrin (10%, 15%, and 20%). Data analysis used a two-way ANOVA test and continued with the DMRT test and scoring test. The results of the powder characteristics produce FM values (5.01 – 5.55); D (0.14 – 0.21 mm); yield (6.70 – 7.11%); powder moisture content (3.26 – 6.37%); brightness level (71.10 – 84.97); redness level (4.14 – 9.13); yellowness level (16.35 – 25.67); water absorption capacity (32.76 – 53.11) and solubility (99.93 – 99.99). Differences in microwave power affect the parameters of degree of fineness (FM), grain size (D), water content, brightness level (L), redness level (a), yellowness level (b), water absorption capacity, and solubility power. Differences in maltodextrin concentration affect the parameters of redness level and solubility. The best combination treatment is 343 W microwave power treatment with a maltodextrin concentration of 20%. Keywords: Drying, Foam mat drying, Microwave, Powder, Red ginger.